2020
DOI: 10.1111/vru.12839
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine‐18 fluorodeoxyglucose positron emission tomography imaging exhibits increased SUVmax at the level of the spinal intumescence in normal dogs

Abstract: Positron emission tomography (PET) imaging utilizing fluorine-18 labeled fluorodeoxyglucose is a relatively new imaging modality in veterinary medicine that is becoming more common for oncological staging and for musculoskeletal imaging. Thus, it is important to identify the normal variations on PET imaging that may be mistaken for pathology. Variation in standardized uptake values (SUVmax) have been anecdotally identified in the spinal cord of dogs undergoing fluorodeoxyglucose (FDG) PET-CT examinations for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Those techniques are even more sensitive than the morphological techniques in the early detection of many diseases. However, they are often combined with CT or Magnetic Resonance (MRI) to provide morphological reference points to the PET or SPECT functional images [160] .…”
Section: Nuclear Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Those techniques are even more sensitive than the morphological techniques in the early detection of many diseases. However, they are often combined with CT or Magnetic Resonance (MRI) to provide morphological reference points to the PET or SPECT functional images [160] .…”
Section: Nuclear Medicinementioning
confidence: 99%
“…SPECT imaging is widely used in Human medicine to diagnose heart ischemia, but this pathology is rare in small animals. Furthermore, in Veterinary medicine there is not a great interest about the study of neuroreceptors, or brain perfusion, thus raising the main interest of SPECT: the study of neurological diseases [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] , [161] , [162] , [163] , [164] , [165] , [166] , [167] , [168] , [169] , [170] , [171] , [172] , [173] , [174] , [175] . Fig.…”
Section: Nuclear Medicinementioning
confidence: 99%
“…However, some studies reported inducing general anesthesia and placing the patient on the PET scanner bed, and then injecting the radiotracer. [24][25][26][27][28] Martinez et al 17) reported that the estimated radiation dose during a PET/CT scan when 18 F-FDG injection was performed before anesthesia induction was higher than the 18 Japanese legislation restricts the 24 h detention period of radioactive animal patients when administering FDG radiopharmaceuticals. Thus, steps of the 18 F-FDG PET imaging protocol, evaluation of the external radiation exposure for veterinary staff in Japan under the applied SPECT system, necessity of the 24 h detention period of animal patients in hospitals, and risk assessment of owners are discussed in this study to increase familiarity and confidence in the PET fields of veterinary staff.…”
Section: Introductionmentioning
confidence: 99%